Association of elevated circulating fibroblast growth factor 21 levels with prevalent and incident metabolic syndrome: The Multi-Ethnic Study of Atherosclerosis. (February 2019) - Ong, Kwok-Leung; McClelland, Robyn L.; Allison, Matthew A.; Kokkinos, John; Wu, Ben J.; Barter, Philip J.; Rye, Kerry-Anne
Abstract: Background and aims: Fibroblast growth factor 21 (FGF21) plays an important role in glucose and lipid metabolism. We have investigated the relationship of plasma FGF21 levels with both prevalent and incident metabolic syndrome (MetS) in participants from the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: 5783 participants from four major ethnic groups (non-Hispanic white, African American, Hispanic American, and Chinese American) were included in the cross-sectional analysis. Longitudinal analysis involved 3479 participants without MetS at baseline, of whom 1100 participants developed incident MetS over 9.2 years. Results: Elevated FGF21 levels were found in participants with prevalent MetS (median [interquartile range] = 189.4 [114.4–302.1] vs . 123.7 [65.9–210.3] pg/mL, p < 0.001) or incident MetS (145.6 [84.9–240.8] vs 112.0 [57.0–194.5] pg/mL, p < 0.001), compared to those without. After adjusting for baseline demographic, socioeconomic and lifestyle factors, as well as cardiovascular risk factors and biomarkers, and compared to the lowest quartile, the highest FGF21 quartile was associated with prevalent MetS (odds ratio 2.80; 95% confidence interval, 2.30–3.40, p < 0.001). Among participants without MetS at baseline, the highest FGF21 quartile was associated with higher risk of incident MetS (hazards ratio 1.76; 95% confidence interval, 1.46–2.12, p < 0.001). Similar results were obtained when assessing ln-transformed FGF21 levels. Overall, no significant interaction was found with age, sex, and race/ethnicity for both prevalent and incident MetS. Conclusions: Higher FGF21 levels significantly predict the development of MetS in an ethnically diverse population followed long term. Further studies are needed to confirm the potential role of FGF21 as a biomarker for MetS. Highlights: Elevated FGF21 levels were associated with prevalent and incident MetS. Elevated FGF21 levels were associated with incident hypertriglyceridemia. The association of FGF21 levels with incident MetS was attenuated with time. No significant interaction was found with age, sex, and race/ethnicity. FGF21 may be a potential MetS biomarker in an ethnically diverse population.